The Influence of Promotion, Price, and Brand Image on Purchase Decisions at Anna Online Shop Cosmetics Store Palopo - Nurjannah*, Nurjannah; Mahmut, Cici; M. Nur, Fratiwi; Merlin, Merlin; Rohani, Nana (Universitas Syiah Kuala, 2024)
Promotion, pricing, and brand image synergistically influence purchasing decisions by capturing consumer attention, offering competitive value, and building trust and loyalty toward the brand. This study aims to analyze the influence of promotion, pricing, and brand image on purchasing decisions at Anna Cosmetics Online Shop in Palopo. The research was conducted on customers who shop at Anna Cosmetics Online Shop in Palopo, with a sample size of 30 people. The method used is non-probability sampling, specifically the saturated sampling technique, where all customers of Anna Cosmetics Online Shop in Palopo were used as samples in this study. Data were collected through interviews and observations using a questionnaire as the data collection tool, with a 5-point Likert scale to measure two main indicators. Data analysis was performed using multiple linear regression techniques. The analysis results show a significance value of 0.000, which is less than 0.05, indicating that the independent variables collectively have a significant influence on the dependent variable. The coefficient of determination (R Square) of 0.630 indicates that 63% of the variation in purchasing decisions (variable Y) can be explained by the promotion (X1), pricing (X2), and brand image (X3) variables, while the remaining 37% is influenced by other variables outside this study.